Aflatoxin M1 in Milk Worldwide from 1988 to 2020: A Systematic Review and Meta-Analysis. (22nd June 2020) - Salari, Nader; Kazeminia, Mohsen; Vaisi-Raygani, Aliakbar; Jalali, Rostam; Mohammadi, Masoud
Abstract : Background . Aflatoxins are found in various types of food and animal feed. Food contamination with aflatoxin toxin is of particular importance today. Various studies have reported different prevalence of aflatoxin M1 in animal milk. Therefore, due to the importance of this toxin, its role in health, and lack of general statistics about it worldwide, the present study aimed to determine the prevalence of aflatoxin M1 in milk worldwide with a systematic review and meta-analysis study. Methods . In this review study, national and international databases were extracted from SID, MagIran, IranMedex, IranDoc, Embase, ScienceDirect, Scopus, PubMed, and Web of Science (ISI) between January 1988 and February 2020. A random effects model was used for analysis, and heterogeneity of studies with an I 2 index was investigated. Data were analyzed using Comprehensive Meta-Analysis (version 2). Results . The prevalence of aflatoxin M1 in milk worldwide from January 1988 to February 2020 in 122 articles with a sample size of 18921 was 79.1% (95% CI: 75.5–82.3%). Regarding the heterogeneity based on metaregression, there was a significant difference between the effect of the year of study (p ≤ 0.001 ) and sample size (p ≤ 0.001 ) with the prevalence of aflatoxin M1 in animal milk. Conclusion . The results of this study show that the prevalence of aflatoxin M1 in milk is high worldwide. Therefore, considering the importance of the milk group and its products, special measures should be taken to protect the ration from aflatoxin molds and milk quality.